How can we interpret the relationship between liquid-liquid phase separation and amyotrophic lateral sclerosis? - Kanekura, Kohsuke; Kuroda, Masahiko (Laboratory investigation, 2022)
One of the critical definitions of neurodegenerative diseases is the formation of insoluble intracellular inclusion body. These inclusions are found in various neurodegenerative diseases such as Alzheimer's disease, amyotrophic lateral sclerosis (ALS), Huntington's disease, Parkinson's disease, and frontotemporal dementia (FTD). Each inclusion body contains disease-specific proteins and is also resistant to common detergent treatments. These aggregates are generally ubiquitinated and thus recognized as misfolded by the organism. They are observed in residual neurons at the affected sites in each disease, suggesting a contribution to disease pathogenesis. The molecular mechanisms for the formation of these inclusion bodies remain unclear. Some proteins, such as superoxide dismutase 1 (SOD1) mutant that causes familial ALS, are highly aggregative due to altered folding caused by point mutations. Still, the aggregates observed in neurodegenerative diseases contain wild-type proteins. In recent years, it has been reported that the proteins responsible for neurodegenerative diseases undergo liquid-liquid phase separation (LLPS). In particular, the ALS/FTD causative proteins such as TAR DNA-binding protein 43 kDa (TDP-43) and fused-in-sarcoma (FUS) undergo LLPS. LLPS increases the local concentration of these proteins, and these proteins eventually change their phase from liquid to solid (liquid-solid phase transition) due to abnormal folding during repetitive separation cycles into two phases and recovery to one phase. In addition to the inclusion body formation, sequestration of essential proteins into the LLPS droplets or changes in the LLPS status can directly impair neural functions and cause diseases. In this review, we will discuss the relationship between the LLPS observed in ALS causative proteins and the pathogenesis of the disease and outline potential therapeutic approaches.